EFEKTIFITAS TEHNOLOGI AUGMENTED REALITY (AR) UNTUK MEMAHAMI GERAKAN SHALAT PADA MATA PELAJARAN FIKIH KELAS 2 MI. ASASUL HUDA RANDEGAN TANGGULANGIN - Farida Hanum M.Pd. (Madaris: Jurnal Guru Inovatif, 2021)
The significant development of information technology has given effects to all aspects, not to mention in education world. However, the utilization of technology has not yet reach its effectivity especially in educational learning. It is common to find learning which still utilize conventional and monotone media in particular religion subject. Thus, it raises the boredom, lack of creativity and difficulties for students to gain academic achievement. The utilization of Augmented reality (AR) technology is one of attempts in utilizing technology for academic learning. Assemblr as one example of Augmented reality, is a new innovative media that can be used in religion subject. Assemblr is an application that is able to create 3D content which can be visualized in Augmented reality technology. In fiqh learning for 2nd grade, Islamic primary school Asasul Huda Randegan, Assemblr is able to be used for understanding praying motion in which commonly taught by conventional media such as whiteboard or pictures, now within utilization of Augmented reality technology, will allow teacher to construct a creative, innovative and interactive learning media.